ผลของโปรแกรมการจูงใจเพื่อการป้องกันการเกิดแผลเบาหวานที่เท้าต่อพฤติกรรมการดูแลเท้าของผู้สูงอายุโรคเบาหวานที่มีภาวะเส้นประสาทส่วนปลายเสื่อม - เพชรัตน์ เขตกระโทก (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this quasi-experimental research was to study the effects of a "Diabetic Foot Ulcer Protection Motivation Program" on the foot care behaviors of elderly diabetic patients with peripheral neuropathy. The Protection Motivation Theory (Rogers, 1983) was applied to the development of the intervention. The sample consisted of 40 diabetic peripheral neuropathy elderly patients who sought treatment at Queen Sirikit Hospital, Chonburi. The first 20 subjects were assigned to a control group and the latter 20 subjects were assigned to an experimental group. The participants from both groups had similar characteristics in terms of gender, age, educational attainment, knowledge regarded to diabetic foot care and degree of diabetic foot risk. The experimental group received the protection motivation program and the control group received routine treatment only. The instruments employed in the study included the intervention, developed by the researcher, "Diabetic Foot Ulcer Protection Motivation Program" comprising four group activities and two individual activities for a total of six activities. Data were collected by using the "Foot care behaviors in elderly Diabetics" questionnaire which had been tested for content validity by 5 experts, thereby obtaining a CVI of .82 and an acceptable reliability at .76. Data were analyzed using descriptive (mean, percentage, standard deviation) and t-test statistics. The research findings can be summarized as follows:1. After receiving the protection motivation program, the mean foot care behavior score of the elderly diabetic patients with peripheral neuropathy in the experiment group was significantly higher than the score before receiving the program (p < .01). 2. After receiving the protection motivation program, the mean foot care behavior score of the elderly diabetic patients with peripheral neuropathy in the experiment group was significantly higher than those who received routine treatment only (p < .01).